2015
DOI: 10.1038/nphoton.2015.94
|View full text |Cite
|
Sign up to set email alerts
|

Flying particle sensors in hollow-core photonic crystal fibre

Abstract: Optical fibre sensors make use of diverse physical effects to measure parameters such as strain, temperature and electric field. Here we introduce a new class of reconfigurable fibre sensor, based on a 'flying-particle' optically trapped inside a hollow-core photonic crystal fibre and illustrate its use in electric field and temperature sensing with high spatial resolution. The electric field distribution near the surface of a multi-element electrode is measured with a resolution of similar to 100 mu m by moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 35 publications
0
76
0
Order By: Relevance
“…In light of the multifunctionality of the hybrid nanocavity, its performance should be critically discussed in details. We compare our design with numerous approaches to nanoscale thermometry, heating and monitoring of molecular events, which have been developed for biomedical, cell biological and chemical applications, as well as for material science, physics, and engineering of nanodevices (i)Despite the diameter of the focused radiation (860 nm) we use in Raman measurements is much greater than the average diameter of NPs (100‐300 nm), most of the collected RS signal (Figure c) originates from the BSA molecules hosted inside the nanocavity (inset in Figure c).…”
Section: Discussionmentioning
confidence: 99%
“…In light of the multifunctionality of the hybrid nanocavity, its performance should be critically discussed in details. We compare our design with numerous approaches to nanoscale thermometry, heating and monitoring of molecular events, which have been developed for biomedical, cell biological and chemical applications, as well as for material science, physics, and engineering of nanodevices (i)Despite the diameter of the focused radiation (860 nm) we use in Raman measurements is much greater than the average diameter of NPs (100‐300 nm), most of the collected RS signal (Figure c) originates from the BSA molecules hosted inside the nanocavity (inset in Figure c).…”
Section: Discussionmentioning
confidence: 99%
“…In the early nineties, Yablonovich's work on the synthesis of artificial photonic crystals drew much interest in these new materials. Since then, photonic crystals have been synthesized by simple chemical methods . Among them, inverse‐opal‐type photonic crystals have been extensively used in photocatalysis due to their open structure .…”
Section: Photonic Crystals and Slow Photonsmentioning
confidence: 99%
“…More recently, it was demonstrated that a photonic band gap PCF with an optically-trapped particle inside the hollow core can be used as a reconfigurable sensor [59]. Electric field and temperature sensing with high spatial resolution were demonstrated with such a configuration [59]. The aforementioned examples demonstrate the potential of PCFs to devise completely new optical fibre sensors.…”
Section: Point Sensors Based On Pcfsmentioning
confidence: 99%
“…The transmission spectrum of a twisted PCF exhibits also a dip whose position changes with axial strain or temperature [57,58]. More recently, it was demonstrated that a photonic band gap PCF with an optically-trapped particle inside the hollow core can be used as a reconfigurable sensor [59]. Electric field and temperature sensing with high spatial resolution were demonstrated with such a configuration [59].…”
Section: Point Sensors Based On Pcfsmentioning
confidence: 99%